The unwanted Muslim Rohingyas of Arakan: Aliens in the homeland and shunned by international community - Ishak, Mohd. Shuhaimi (2013)

(untitled)
Myanmar is often inundated by inter-ethnic tensions. In June 2012, a spate of killings and violence broke out in Arakan, between the Muslim minority Rohingyas and the Arakanese Buddhists resulting in many deaths and thousands of people made homeless and living in appalling conditions. Muslim Rohingyas have been in Arakan for decades but because of the country’s systematic and endemic discriminatory policy, they are denied citizenship, restricted in movement, forced into labour and evicted. This study endeavours to look into the historical and present perspectives of the Muslim minority in Myanmar who have suffered and have been persecuted hard, viewed as illegal immigrants by both Myanmar and neighbouring countries. The study is of utmost importance as it highlights the plight of a minority group. Myanmar and the international community need to make fundamental changes in their attitudes to allow a ray of hope for improved conditions for the Rohingyas.